What does it mean to be an ‘engaged university’? Reflections from a university and school-community engagement project - Cherrington, Avivit M; Scheckle, Eileen; Khau, Mathabo; De Lange, Naydene; Du Plessis, Andre (Education, citizenship and social justice, 2019)
This article seeks to address what it means to be an ‘engaged’ university and, in so doing, to contribute to current discourses – in a fast growing field – about how to collaborate with communities for meaningful social transformation. As a group of researchers from the faculty of education in a South African university, we share our thinking and the theoretical notions that underpinned our planning and executing of a 3-year engagement with a rural secondary school. In asking ‘How might dialogic engagement of the university community and the community the university serves, enable agency towards active citizenship in the context of education?’, a collaborative engagement project between and within a school-community and the university was initiated. In this conceptual article, we unpack and discuss a critical university and school-community engagement with, and interpretation of, three key concepts that underpinned it: dialogic engagement, community and active citizenship. We conclude with a discussion on how we put these three key elements into practice. It is therefore argued that to be truly engaged requires constant dialogue, reflection, and the intentionality and commitment of all parties towards collaboration that is aimed at promoting mutual learning through socially just processes. Such university and school-community engagement is key in addressing complex social issues requiring collaborative intervention to enable social transformation.